Tinjauan Pendidikan Multikultural dalam Al Hujurat Ayat 13 - Devi Agustina (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2022)
This research was conducted with the aim of examining the multicultural education contained in the letter al Hujurat verse 13. The questions to be answered in this study are: 1) What are the multicultural education contained in the letter al Hujurat verse 13. To answer this question, this study uses library research, namely research whose research object is carried out through various library sources. This method the author uses to explain the content of multicultural education from al Hujurat verse 13. The results of the study show that multicultural education in surah al Hujurat verse 13 includes gender equality, ethnic and national differences, and equal degrees. Allah, created humans consisting of men and women by making them with various conditions between ethnicity, race, class, skin color, language is not a reason but for them to know each other to spread love and peace, and help each other in matters kindness, mutual respect, and live in harmony with full tolerance for the diversity that exists